2013
DOI: 10.1007/s10597-013-9639-x
|View full text |Cite
|
Sign up to set email alerts
|

Measuring System of Care Core Values in a Behavioral Health System of Care

Abstract: The Comprehensive Services for Children and Their Families or System of Care (SOC) is the largest mental health project ever conducted by the US federal government. These programs are based on a value-driven framework that includes: child/youth centered and family driven practice, community-based practice, and culturally competent practice (Stroul and Friedman in A system of care for children and youth with severe emotional disturbances, Georgetown University Child Development Center, CASSP Technical Assistanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…At the policy level, the application of system-of-care principles is reflected in how services are funded (e.g., integrated funding from multiple organizations or sources), developed (e.g., generation of varied community-based services and supports), organized (e.g., single points of entry, co-location of staff), and managed (e.g., integrated quality monitoring and new service development across systems). Several studies have shown that communities vary extensively in their adherence to system-of-care principles at the policy level (Greenbaum et al, 2011 ; Vinson et al, 2001 ). Research has also shown that greater adherence to system-of-care principles at the policy level increases access to mental health services, continuity of care, and use of less restrictive forms of care (Bickman, 1996 ; Bickman et al, 1997 ).…”
Section: Introductionmentioning
confidence: 99%
“…At the policy level, the application of system-of-care principles is reflected in how services are funded (e.g., integrated funding from multiple organizations or sources), developed (e.g., generation of varied community-based services and supports), organized (e.g., single points of entry, co-location of staff), and managed (e.g., integrated quality monitoring and new service development across systems). Several studies have shown that communities vary extensively in their adherence to system-of-care principles at the policy level (Greenbaum et al, 2011 ; Vinson et al, 2001 ). Research has also shown that greater adherence to system-of-care principles at the policy level increases access to mental health services, continuity of care, and use of less restrictive forms of care (Bickman, 1996 ; Bickman et al, 1997 ).…”
Section: Introductionmentioning
confidence: 99%
“…There is a duality in the patient–provider relationship whereby cultural discrepancies are felt on both ends ( Patel et al, 2018 ; Sakai et al, 2019 ; Wald et al, 2014 ), and ‘cultural safety’ may be a potential solution in addressing these discrepancies. Cultural safety has recently emerged as an approach that holistically considers the role of social and historical contexts, as well as structural and interpersonal power imbalances, in influencing the healthcare experiences of patients ( Anishnawbe Health Toronto, 2011 ; National Aboriginal Health Organization, 2009 ).…”
Section: Introductionmentioning
confidence: 99%